2016
DOI: 10.1007/s12035-016-9877-3
|View full text |Cite
|
Sign up to set email alerts
|

IgA/IgM responses to tryptophan and tryptophan catabolites (TRYCATs) are differently associated with prenatal depression, physio-somatic symptoms at the end of term and premenstrual syndrome

Abstract: There is some evidence that lowered tryptophan and an activated tryptophan catabolite (TRYCAT) pathway play a role in depression, somatoform disorder, and postpartum blues. The aim of this study is to delineate the associations between the TRYCAT pathway and premenstrual syndrome (PMS) and perinatal depressive and physio-somatic symptoms. We examine the associations between end of term serum IgM and IgA responses to tryptophan and 9 TRYCATs in relation to zinc, C-reactive protein (CRP), and haptoglobin and pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
34
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 40 publications
(36 citation statements)
references
References 87 publications
2
34
0
Order By: Relevance
“…68,69 PMS is comorbid with other immuno-inflammatory conditions, including major depression, bipolar disorder, as well as perinatal depression. 43,70 The fourth major finding of this study is that increased NOx levels are associated with IgM responses to NO adducts, but not NO 2 tyrosine, whilst the latter is associated with increased IgM responses to MDA. Different mechanisms may explain why increased NO production is associated with an index of nitrosylation (NO) but not nitration (NO 2 ).…”
Section: Discussionmentioning
confidence: 56%
“…68,69 PMS is comorbid with other immuno-inflammatory conditions, including major depression, bipolar disorder, as well as perinatal depression. 43,70 The fourth major finding of this study is that increased NOx levels are associated with IgM responses to NO adducts, but not NO 2 tyrosine, whilst the latter is associated with increased IgM responses to MDA. Different mechanisms may explain why increased NO production is associated with an index of nitrosylation (NO) but not nitration (NO 2 ).…”
Section: Discussionmentioning
confidence: 56%
“…By significantly reducing the incidence of PDS and postpartum blues, DEX would seem to be acting on the pathways primed by historical factors such as stress during pregnancy, life stress events, and domestic violence, which the data in the present study indicate to be risk factors for PDS. It is also of note that DEX decreased the risk of both postpartum blues and PDS, proposed by some researchers to have distinct pathophysiologies . Although DEX showed a trend to decrease PDS and postpartum blues in women reporting severe stress during pregnancy, only those reporting a moderate level of such pressure/stress showed a significant decrease in PDS and postpartum blues incidence.…”
Section: Discussionmentioning
confidence: 85%
“…It is also of note that DEX decreased the risk of both postpartum blues and PDS, proposed by some researchers to have distinct pathophysiologies. 47 Although DEX showed a trend to decrease PDS and postpartum blues in women reporting severe stress during pregnancy, only those reporting a moderate level of such pressure/stress showed a significant decrease in PDS and postpartum blues incidence. This requires further confirmation and investigation because it could suggest the existence of distinct physiologic processes that depend on the levels of reported stress.…”
Section: Discussionmentioning
confidence: 92%
“…Previous studies found that physio‐somatic symptoms of depression rather than primary mood symptoms per se may be related to alterations in TRYCATS (the tryptophan catabolite) pathways, which lead to increased activity of indoleamine 2,3‐dioxygenase disorders in kynurenine aminotransferase activity (Anderson, Berk, & Maes, ; Anderson, Maes, & Berk, ). However, Roomruangwong, Kanchanatawan, Sirivichayakul, Anderson, et al () indicated that increased TRYCATS activity cannot predict perinatal depression; in contrast, Maes et al () found a significant relationship between increased TRYCATS levels and postpartum blues (mild mood and physio‐somatic postpartum symptoms). Whether childbirth changes TRYCATS pathways activity or not, these contradictory or paradoxical results imply that the underlying biological mechanisms have not been substantially identified, regardless of the clinical phenotype subtypes.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies found that physio-somatic symptoms of depression rather than primary mood symptoms per se may be related to alterations in TRYCATS (the tryptophan catabolite) pathways, which lead to increased activity of indoleamine 2,3-dioxygenase disorders in kynurenine aminotransferase activity (Anderson, Berk, & Maes, 2014;Anderson, Maes, & Berk, 2012). However, Roomruangwong, Kanchanatawan, Sirivichayakul, Anderson, et al (2017) indicated that increased TRYCATS activity cannot predict perinatal depression; in contrast, Maes et al (2002) that underlie the different perinatal depressive-symptom subtypes at different pregnancy stages.…”
Section: Distributions Of Perinatal Depressive-symptom Phenotypes Amentioning
confidence: 99%